Pain Management after Bilateral Mastectomy Surgery with Continued Intravenous Ketamine: A Case Report - Zulfikar Djafar; A. Husni Tanra (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Ketamine is recommended as postoperative analgesia because ketamine is a classic anesthetic agent that is available in almost all hospitals, including hospitals with limited resources. This study aims to describe the continuous use of intravenous ketamine as postoperative pain management in a bilateral mastectomy. Case presentation: A woman, 35 years old, was admitted to the hospital with complaints of lumps in both breasts. On physical examination, the patient looked weak, with blood pressure 120/70 mmHg, pulse 105x/minute, respiratory rate 18x/minute, temperature 36.8ºC, and numeric rating scale (NRS) 7/10. In the thoracic region, mammary dextra, there is a lump the size of a fixed tennis ball, 15 cm in diameter, and the skin around the lump looks red with a dry wound. On palpation, there is tenderness and hardness; mamma sinistra has a lump the size of a melon, 20 cm in diameter, with an ulcer that is still wet. On palpation, there is tenderness and hardness, and fixation. The patient was diagnosed as mammary tumor dextra et sinistra, suspected malignancy, and a simple bilateral mastectomy was performed. The anesthetic technique used during the operation was general anesthesia with endotracheal intubation (GETA). The premedication given was dexamethasone 10 mg intravenously, midazolam 3 mg intravenously, and fentanyl 100 mcg intravenously. Postoperative pain management using ketamine 0.15 mg/kgBW was given a bolus, followed by 0.1 mg/kgBW/hour. Conclusion: The use of ketamine in postoperative bilateral mastectomy can reduce pain intensity and have minimal side effects.